Structure and irregularities of surface of fried batters studied by fractal dimension and lacunarity analysis. (July 2016) - Rahimi, Jamshid; Ngadi, Michael O.
Graphical abstract: Highlights: Fractals and lacunarity were used to study the irregularities of fried batters. Fractal dimension showed a high correlation with surface roughness of fried batters. FD of SEM images of wheat flour batters was higher than rice flour batters. Lacunarity showed a uniform range of ruptures generated on the surface of batters. Abstract: Fractal dimension and lacunarity were applied to study the structure and irregularities of fried batters. Using scanning electron microscopy, images of batter surfaces were captured, and analyzed via ImageJ software. Fractal dimension (FD) ranged between 1.79 and 1.81. Higher amount of wheat flour in batter preparation resulted in higher FD values compared to batters with higher amount of rice flour. FD significantly (P < 0.05) increased during frying. There was a high positive correlation between FD and fat uptake for all batter formulations (|r| = 0.91-0.99) that means that surface roughness is an important factor affecting the amount of fat remaining on the surface of batters. Lacunarity, as a measure of degree of heterogeneity of batter ruptures, ranged between 1.19 and 1.25. The lacunarity results showed that the size and shape of ruptures generated on the surface of batters during frying was approximately uniform.